Optimalisasi Rute Distribusi Peralatan Elektronik: Inovasi Metode Saving Matrix dan Nearest Neighbor - Khoerun Nisa Safitri; Asrul Fole; Nurul 'Aini (Fakultas Teknik Universitas Ibnu Sina, 2025)
This research focuses on evaluating and comparing the effectiveness of the Saving Matrix and Nearest Neighbor techniques for optimizing the distribution routes of electronic devices in Batam. Additionally, it assesses these methods against the current approach utilized by the company. A quantitative methodology was adopted, utilizing data that encompasses customer locations, shipment volumes, and vehicle capacities. The findings reveal that the Saving Matrix method yields the highest efficiency, achieving a total travel distance of 54.3 km, a delivery duration of 5.2 hours, and an operational expenditure of Rp785,000. Conversely, the Nearest Neighbor method resulted in a distance of 62.7 km and a cost of Rp905,000, while the company's existing method recorded the longest distance at 68.5 km and the highest cost of Rp970,000. These results indicate that the Saving Matrix method is superior in optimizing both routes and load distribution. This study contributes to logistics planning by highlighting the significance of heuristic approaches in addressing vehicle routing challenges. It is advisable for companies to consider implementing algorithmic methods in their distribution strategies. Future studies should aim to develop models using metaheuristic techniques and take into account dynamic factors such as customer service time frames and real-time traffic conditions for enhanced accuracy.